Telecommunications and Empire. - Hills, Jill. (Champaign : University of Illinois Press, 2007)
"This study documents attempts by the United States and other governments to direct, replace, and bypass international telecommunications institutions. The results are indirect control over foreign domestic markets, government management of private corporations, and government protection of its own domestic communication market. Hills reveals that the motivation behind these powerful, regulatory efforts on person-to-person communication lies in the unmatched importance of communication in the world economy."--Jacket.
Global Mobile Personal Communications Systems -- Bypassing the ITU-"Accounting Rates" -- The Commonwealth Model -- The U.S. Backlash -- ICANN: Bypassing the ITU -- Conclusion -- 5. The World Bank and Privatization -- Background -- U.S. Power over the World Bank -- The Early Years of the World Bank's Privatization Thesis -- The World Bank's Privatization Thesis-1980s -- The Concept of Privatization and the British Model -- Telecommunications Lending-The First Years -- The Impact of the World Bank's Privatization Thesis -- Conclusion -- 6. GATT/WTO and Telecommunications
Description based upon print version of record.
GATT and the International Trade Organization
Includes bibliographical references (p. [257]-281) and index.
JSTOR
Keywords: Telecommunication policy -- United States; Telecommunication -- International cooperation -- Political aspects; Télécommunications -- Politique gouvernementale -- États-Unis.; Télécommunications -- Coopération internationale -- Aspect politique; TECHNOLOGY & ENGINEERING / General; Telecommunication policy; Telecommunication -- International cooperation -- Political aspects; United States; Telekommunikationspolitik; USA; Telecommunications -- Cooperation internationale -- 1945-1990.; Politique des telecommunications -- États-Unis -- 1945-1990.